2010 IEEE Information Theory Workshop 2010
DOI: 10.1109/cig.2010.5592719
|View full text |Cite
|
Sign up to set email alerts
|

An extension of Massey scheme for secret sharing

Abstract: We consider an extension of Massey's construction of secret sharing schemes using linear codes. We describe the access structure of the scheme and show its connection to the dual code. We use the g-fold joint weight enumerator and invariant theory to study the access structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It was shown in [2], [4] that any pair of nested linear codes C 2 ⊂ C 1 ⊂ F n q can be used for constructing a linear ramp secret sharing scheme [1], [9]. Recently, Kurihara et al [6] showed that the smallest number of shares required for an adversary to illegitimately obtain at least t log 2 q bits of information is exactly expressed by the t-th relative generalized Hamming weight (RGHW) of C ⊥ 1 ⊂ C ⊥ 2 proposed by Luo et al [7].…”
Section: Introductionmentioning
confidence: 90%
“…It was shown in [2], [4] that any pair of nested linear codes C 2 ⊂ C 1 ⊂ F n q can be used for constructing a linear ramp secret sharing scheme [1], [9]. Recently, Kurihara et al [6] showed that the smallest number of shares required for an adversary to illegitimately obtain at least t log 2 q bits of information is exactly expressed by the t-th relative generalized Hamming weight (RGHW) of C ⊥ 1 ⊂ C ⊥ 2 proposed by Luo et al [7].…”
Section: Introductionmentioning
confidence: 90%
“…Both secret and shares are traditionally classical information. There exists a close connection between secret sharing and classical error-correcting codes [4,12,15,16,29,34,44].…”
Section: Introductionmentioning
confidence: 99%
“…Both secret and shares are traditionally classical information. There exists a close connection between secret sharing and classical error-correcting codes [3,7,10,11,19,23,31].…”
Section: Introductionmentioning
confidence: 99%